Fundamentos de geometria hiperbólica - Perez, Carlos Martinez [UNESP] (2015)
Our work, about the foundations of Hyperbolic Geometry, presents the historical development of this geometry from the controversy around the fifth postulate of Euclid. It will also be treated the Hilbert axiomatic and some results of Neutral Geometry, before introducing the Hyperbolic Geometry and its infinite many parallels. After the discussion of its basic concepts and theorems, we present the Upper Half Plane Model, way to use the Group Theory and the Möbius Transformation, algebraic tools to facilitate the introduction of the metric and Hyperbolic Trigonometry. The objective of this work is to provide high school teachers of Mathematics and Physics the opportunity for a first contact with Hyperbolic Geometry